Strengthening accountability to end preventable maternal deaths. (October 2015) - Mathai, Matthews; Dilip, Thandassery R.; Jawad, Issrah; Yoshida, Sachiyo
Abstract: The present paper describes the ongoing efforts to revitalize the accountability of national governments toward preventable maternal deaths. Maternal death reviews are included in the national health policies of the majority of countries contributing 95% of global maternal deaths. However in actual practice, the extent of implementation and follow-up of recommended actions on lessons learnt from maternal death reviews is inadequate. This paper describes and discusses the role of the Maternal Death Surveillance and Response (MDSR) system in strengthening accountability and ending preventable maternal deaths. MDSR provides a surveillance tool for timely information on where, when, and why maternal deaths occur, builds on maternal death reviews, and includes the missing "response" component for improving quality of care and preventing maternal deaths.